The Role of Social Comparison and Online Social Support in Social Media Addiction Mediated by Self-Esteem and Loneliness (European Journal of Mental Health, 2024)
Introduction: The diversity of information on social media provides a ubiquitous possibility for social comparison. Online social comparisons have both detrimental and beneficial effects; besides lowering one’s self-esteem, heightening loneliness and addiction, they also bring together people with similar interests which may offer a form of social support.Aims: This study examines a path model for understanding the link between social comparison and social media addiction while examining online social support, loneliness, and self-esteem.Methods: Hungarian university students (N = 201, 70.6% women, aged between 18 and 30 years, SD = 2.77) completed an online survey in the spring of 2022.Results: The final path model suggests that social comparison can directly contribute to social media addiction. This link was mediated by loneliness and self-esteem, resulting in a path with different outcomes: a) social comparison may strengthen loneliness (β = .22, p < .001) which can lead to lower self-esteem (β = .60, p < .001), and b) social comparison may have a negative effect on self-esteem (β = -.22, p < .001) which can reduce social media addiction (β = -.26, p < .001). In addition, social comparison may help obtain online social support (β = .15, p < .050) which can reduce loneliness (β = -.41, p < .001) but increase the likelihood of addiction (β = .26, p < .001).Conclusions: These findings draw attention to the double-edged sword of social comparison and online social support: we need to learn to consciously manage online social comparison tendencies.